Fresno County Bar Association Bar Banquet at TorNino's - Watkins, Howard::::::::: (1984)
Back up singers William J. Smith, Val Saldana, Jim Lambe, Suzanne Paboojian, Robert Jones and lead singer Mary Louise Frampton as Rosie and the Supremes Singing "Change the Law" to the tune of the Supremes song "Baby Love